(untitled) (Journal of Atomic and Molecular Sciences, 2014)
Applying scaling theory of polyelectrolyte adsorption, and according to ratio of the dielectric constant between the medium and the substrate, and taking into account strong interaction between polyelectrolytes of multivalency adsorption, we proposed a scaling theory of the approximation method on a repulsive charged surface. It is divided into two kind phase diagrams that one is qualitatively different. This shows when the surface charge density is low (or the bulk counterion density is high), the surface and the bulk counterion density are almost the same. Once the surface charge density is high enough, counterions condense on the surface. In this regime, polyelectrolytes of lower valency form a correlated many-chain state. As their valency is high enough, the state turns out to be single-chain because of stronger repulsion between neighboring chains.